Effects of Autogenic Training technique on nonlinear heart rate variability (Research, Society and Development, 2022)
Objective: The present study intended to analyze the effects of a relaxation technique called autogenic training, on nonlinear heart rate variability, with the hypothesis that the relaxation in question is capable of promote greater synergism between the sympathetic and the parasympathetic nervous system, thus avoiding high levels of stress and future complications. Methods: To this end, a controlled, non-randomized, open and cross-sectional clinical study was conducted, with 19 participants who underwent a single session of autogenic training. Results: The results show that both groups (experimental and placebo) had p-value